Toner manufacturing method
By using crystalline and amorphous resins with specific melting and softening points in the -toner and forming a specific matrix domain structure, the image glossiness problem caused by domain aggregation in the low-energy fixation process is solved, and the effects of low-temperature fixation and high glossiness are achieved.
Patent Information
- Application Number
- JP2021051399
- Authority / Receiving Office
- JP · JP
- Patent Type
- Patents
- Current Assignee / Owner
- Filing Date
- 2021-03-25
- Publication Date
- 2025-04-21
- Estimated Expiration
- 2041-03-25
AI Technical Summary
Existing-toner may experience domain aggregation during low energy fixation, resulting in image glossiness problems.
The -toner particles containing the first and second resins are used, the first resin is a crystalline resin with a melting point of 50°C or above, 90°C or below, the second resin is an amorphous resin with a softening point of 10°C or above, and a matrix domain structure is formed by cross-linking treatment, and the average roundness of the domain is between 0.40 and 0.80.
By controlling the domain structure and roundness, the domain aggregation of the -toner during the fixation process is suppressed, and low-temperature fixation and good image glossiness are achieved.
Smart Images

Figure 0007665374000011 
Figure 0007665374000001 
Figure 0007665374000002
Abstract
Description
[Technical field]
[0001] The present invention relates to a toner used in an electrophotographic system, an electrostatic recording system, an electrostatic printing system, and a toner jet system. Manufacturing method Regarding. [Background technology]
[0002] In recent years, as full-color electrophotographic copiers have become more widespread, there has been an ever-increasing demand for faster printing and energy conservation. To accommodate high-speed printing, technology that melts toner more quickly in the fixing process is being considered. Also, to improve productivity, technology that shortens the time for various controls during a job and between jobs is being considered. Also, as an energy-saving measure, technology that fixes toner at a lower temperature is being considered in order to reduce power consumption in the fixing process. It is known that a toner having a binder resin mainly composed of a crystalline resin having sharp melting properties has excellent low-temperature fixing properties compared to a toner having a binder resin mainly composed of an amorphous resin. For example, Patent Document 1 proposes a toner that has excellent fixing properties, image density, and image glossiness by forming a matrix domain structure (sea-island structure) having a matrix containing a crystalline resin and domains containing an amorphous resin and a colorant, and by setting the domain diameter and storage modulus of the islands within a predetermined range. Patent Document 2 also proposes a toner that can be fixed with low energy and can obtain an image that is resistant to external forces such as rubbing and scratching by forming a matrix domain structure having a matrix containing a crystalline resin with a predetermined melting point range and domains containing an amorphous resin. [Prior art documents] [Patent documents]
[0003] [Patent Document 1] JP 2014-66994 A [Patent Document 2] JP 2014-142632 A Summary of the Invention [Problem to be solved by the invention]
[0004] The toners described in Patent Documents 1 and 2 have a matrix domain structure, and a crystalline resin having sharp melting properties forms the matrix, so that they have excellent fixing properties with low energy. However, under certain conditions, there are cases where the domains aggregate when the toner is melted in the fixing process, causing problems with the gloss of the image after fixing. [Means for solving the problem]
[0005] The present invention relates to a toner having toner particles containing a binder resin. Manufacturing method And, The production method comprises the steps of: A melt-kneading step of melt-kneading the first resin and the second resin to obtain a resin composition; and a grinding step of grinding the obtained resin composition; The toner particles are obtained through The toner particles contain The binder resin contains a first resin and a second resin. Wait , The first resin comprises: (i) Contains acrylonitrile units Crystalline Vinyl It is a resin, (ii) the melting point Tp is 50°C or higher and 90°C or lower; The second resin is (i) Contains acrylonitrile units Amorphous Styrene Acrylic It is a resin, (ii) the softening point Tm is 10° C. or more higher than the Tp; The toner particles are characterized in that, when a cross section of the toner particles is observed by a transmission electron microscope, the first resin of A matrix and the second resin. of A matrix domain structure having a domain and The toner is characterized in that the average circularity of the domains is 0.40 or more and 0.80 or less. Manufacturing method Regarding. Effect of the Invention
[0006] According to the present invention, a crystalline resin having a matrix domain structure and sharp melting properties forms the matrix, and the circularity of the domain formed by the amorphous resin is within a predetermined range, so that aggregation of the domains when the toner is melted in the fixing process can be suppressed, and both low-temperature fixing ability and good gloss images can be achieved. [Brief description of the drawings]
[0007] [Figure 1] FIG. 2 is a schematic diagram of a surface treatment device suitable for treating the surface of a toner. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0008] Hereinafter, an embodiment of the present invention will be described in detail.
[0009] In the present disclosure, the expressions "XX or more and YY or less" and "XX to YY" representing a numerical range mean a numerical range including the endpoints, that is, the lower limit and the upper limit, unless otherwise specified.
[0010] The (meth)acrylic acid ester means an acrylic acid ester and / or a methacrylic acid ester.
[0011] When numerical ranges are stated in stages, the upper and lower limits of each numerical range can be combined in any way.
[0012] The term "monomer unit" refers to the reacted form of a monomer substance in a polymer. For example, one section of carbon-carbon bond in the main chain of a polymer in which a vinyl monomer is polymerized is considered to be one unit. The vinyl monomer can be represented by the following formula (Z).
[0013] [ka]
[0014] In the formula (Z), Z1 represents a hydrogen atom or an alkyl group (preferably an alkyl group having 1 to 3 carbon atoms, more preferably a methyl group), and Z2 represents an arbitrary substituent.
[0015] The present invention provides a toner having toner particles containing a binder resin, The binder resin contains a first resin and a second resin, The first resin is (i) a crystalline resin, and (ii) has a melting point Tp of 50° C. or more and 90° C. or less, The second resin is (i) an amorphous resin, and (ii) has a softening point Tm that is 10° C. or more higher than the Tp. The toner particles are characterized in that, when observed in cross section with a transmission electron microscope, they have a matrix domain structure having a matrix containing the first resin and a domain containing the second resin, and the average circularity of the domain is 0.40 or more and 0.80 or less.
[0016] The present inventors have found that in a toner having a matrix domain structure as described above, it is possible to achieve both low-temperature fixability and good gloss images by controlling the matrix domain structure of the crystalline resin and the amorphous resin, the area occupied by the crystalline resin, and the circularity of the domain. The present inventors speculate that the reason for this is as follows.
[0017] By using a toner having a domain shape with a predetermined circularity, it is possible to suppress the aggregation of domains in the molten state of the toner in the fixing process of electrophotography, and the low-temperature fixing property is also utilized, so that it is considered that good low-temperature fixing property and glossy image can be achieved at the same time. If the circularity is too high, the interface area is small, so that the domains tend to move easily in the matrix, and the effect of reducing the interface area may make the domains more likely to aggregate. In addition, the sharp melting property of the crystalline resin is not fully utilized due to the small interface area, and low-temperature fixing property may be reduced. If the circularity is too low, the interface area between the matrix and the domain becomes large, and it is considered that the gloss is reduced due to reasons such as the suppression of domain movement during melting.
[0018] When the average circularity of the domain is 0.4 or more and 0.8 or less, both low temperature fixability and good gloss image can be achieved.
[0019] Here, the circularity of the domain is affected by the compatibility of the material constituting the domain and the material constituting the matrix. When the compatibility is low, the circularity is increased, and when the compatibility is high, the circularity is decreased. Therefore, it is possible to control the domain shape by controlling the compatibility. In addition, the kneading temperature and kneading time in the melt kneading process, the screw rotation speed, and the stirring rotation speed in the aggregation process can also be mentioned as means for controlling the circularity. For example, lowering the kneading temperature to a temperature close to the softening point Tm can be expected to have the effect of lowering the circularity.
[0020] Here, the "circularity of a domain" is defined as the circularity of a domain in the cross-sectional observation image obtained by a transmission electron microscope, where S is the area of the domain and L is the perimeter of the domain, (4π×S / L 2 ) is calculated using the formula:
[0021] The crystalline resin forming the matrix may be a known crystalline resin. Examples include crystalline vinyl resin, crystalline polyester resin, crystalline polyurethane resin, and crystalline polyurea resin. Other examples include ethylene copolymers such as ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methacrylic acid copolymer, and ethylene-acrylic acid copolymer. From the viewpoint of low-temperature fixability, crystalline vinyl resin and crystalline polyester resin are preferred.
[0022] On the other hand, the amorphous resin forming the domain may be any known amorphous resin, and is preferably a polyester resin, a styrene-acrylic resin, or a hybrid resin thereof from the viewpoints of low-temperature fixability and fixation separation property.
[0023] The domains preferably have a number-average circle-equivalent diameter of 20 nm to 500 nm. When the number-average circle-equivalent diameter of the domains is longer than 500 nm, the crystalline resin contained in the matrix melts during low-temperature fixing of the toner, but the amorphous resin contained in the domains does not melt easily. As a result, the domains are not easily fixed to paper, which tends to result in poor fixing. On the other hand, during high-temperature fixing, the viscosity of the matrix containing the molten crystalline resin tends to decrease, which tends to reduce hot offset resistance and winding resistance.
[0024] In addition, when the number-average diameter of the domains is less than 20 nm, or when the crystalline resin and the amorphous resin are mutually mixed to form a uniform structure without a matrix domain structure, the hot offset resistance and winding resistance are likely to be deteriorated. Furthermore, the sharp melting property of the crystalline resin is likely to be lost, and the low-temperature fixability is likely to be deteriorated.
[0025] Here, the "number-average diameter of circles equivalent to domains" is defined as the average value of the diameters of perfect circles whose area corresponds to S for each domain, where S is the area of each domain in the cross-sectional image observed by a transmission electron microscope.
[0026] Methods for controlling the number-average equivalent circle diameter of the domains include the relationship between the SP values (described later) of the matrix and domain resins, the kneading temperature and screw rotation speed in the melt kneading process, and the stirring rotation speed in the aggregation process. If the SP values of the matrix and domain resins are close, the compatibility between the matrix and domains increases, and the number-average equivalent circle diameter of the domains decreases. In addition, increasing the screw rotation speed or stirring rotation speed increases the shear force on the resin, and the number-average equivalent circle diameter of the domains decreases.
[0027] In the toner, it is preferable that the standard deviation of the circularity of the domain containing the second resin is 0.15 or more.
[0028] As mentioned above, by using a toner with a suitable degree of circularity in the domains, it is expected that the aggregation of the domains can be suppressed when the toner is in a molten state during the fixing process of electrophotography. In addition, by having a relatively wide distribution of domain circularity with a standard deviation of 0.15 or more, the domains of different shapes fill in the gaps when the toner is in a molten state during the fixing process, which is expected to improve the uniformity of the domain arrangement and further improve gloss.
[0029] Examples of a method for controlling the standard deviation of the circularity of the domain include the kneading temperature and kneading time in the melt-kneading step, the screw rotation speed, the stirring rotation speed in the aggregation step, etc. In addition, as a means for increasing the standard deviation, it is also effective to use toner particles having different kneading conditions such as temperature in combination.
[0030] In the toner, when the SP value of the first resin is SPc and the SP value of the second resin is SPa, it is preferable that the SPc and the SPa satisfy 0.5≦|SPc−SPa|≦2.0.
[0031] Here, the SP value is an abbreviation for soluble parameter, which is a value that serves as an index of solubility. It is calculated according to the method proposed by Fedors.
[0032] In the present invention, the unit of the SP value is (J / cm 3 ) 0.5 However, 1 (cal / cm 3 ) 0.5 =2.045×10 3 (J / cm 3 ) 0.5 by (cal / cm 3 ) 0.5 can be converted to units of
[0033] In the toner having the matrix domain structure, by using a toner whose domain shape exhibits a predetermined circularity, it is believed that aggregation of domains can be suppressed when the toner is in a molten state in the electrophotographic fixing process, and low-temperature fixing properties can also be utilized, thereby achieving both good low-temperature fixing properties and glossy images.
[0034] The circularity of the domain is affected by the compatibility between the material that composes the domain and the material that composes the matrix. When the compatibility is low, the circularity is higher, and when the compatibility is high, the circularity is lower. If |SPc-SPa| is less than 0.5, the circularity of the domain becomes too low, which increases the interfacial area between the matrix and the domain, and it is thought that this causes a decrease in gloss due to reasons such as the suppression of domain movement during melting.
[0035] Furthermore, if |SPc-SPa| is greater than 2.0, the circularity becomes too high, the interfacial area becomes small, the domains become more mobile in the matrix, and the effect of reducing the interfacial area may lead to the aggregation of the domains. In addition, the sharp melting properties of the crystalline resin are not fully utilized due to the small interfacial area, and low-temperature fixability may also decrease.
[0036] In cross-sectional observation using the transmission electron microscope, it is preferable that the first resin occupies 35% or more and 70% or less of the total area of the matrix and the domain.
[0037] In a toner having a matrix domain structure composed of a matrix containing a crystalline resin and a domain containing an amorphous resin, the effect can be obtained when the ratio of the crystalline resin to the total area of the matrix and the domain combined is in the range of 35% to 70%. If the ratio of the crystalline resin is less than 35%, the above-mentioned matrix domain structure is reversed, and low-temperature fixing properties deteriorate. Also, if the ratio of the crystalline resin is more than 70%, the viscosity of the matrix containing the molten crystalline resin tends to decrease, and hot offset resistance tends to decrease.
[0038] In the toner, it is preferable that the first resin has a monomer unit represented by the following formula (1) from the viewpoint of maintaining good storage stability.
[0039] It is also preferable that the first resin contains a resin containing a nitrile group and the second resin contains a resin containing a nitrile group, since this is expected to have an effect of improving gloss through control of compatibility.
[0040] It is also preferable that the second resin is one or more resins selected from the group consisting of amorphous polyesters, amorphous vinyl resins, and hybrid resins having an amorphous polyester portion and an amorphous vinyl portion, since this is expected to have the effect of improving gloss by controlling compatibility.
[0041] <Ingredients description> Materials that can be used to practice the present invention are described in detail below.
[0042] <First Resin> The binder resin contains a first resin, and the first resin is a crystalline resin.
[0043] As the crystalline resin, a known crystalline resin can be used. For example, crystalline vinyl resin, crystalline polyester resin, crystalline polyurethane resin, and crystalline polyurea resin can be mentioned. In addition, ethylene copolymers such as ethylene-vinyl acetate copolymer, ethylene-methyl acrylate copolymer, ethylene-ethyl acrylate copolymer, ethylene-butyl acrylate copolymer, ethylene-methyl methacrylate copolymer, ethylene-methacrylic acid copolymer, and ethylene-acrylic acid copolymer can also be mentioned.
[0044] From the viewpoint of low-temperature fixability, crystalline vinyl resins and crystalline polyester resins are preferred.
[0045] Furthermore, the first resin is preferably a vinyl resin, and further preferably has a first monomer unit represented by the following formula (1). The first resin is preferably a crystalline resin having a monomer unit represented by the following formula (1).
[0046] [ka] [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms.
[0047] The first monomer unit represented by the above formula (1) has R 1 The alkyl group has 18 to 36 carbon atoms, and the presence of this portion makes it easier for the compound to exhibit crystallinity.
[0048] Examples of (meth)acrylic acid esters having an alkyl group having 18 to 36 carbon atoms include (meth)acrylic acid esters having a straight-chain alkyl group having 18 to 36 carbon atoms [stearyl (meth)acrylate, nonadecyl (meth)acrylate, eicosyl (meth)acrylate, heneicosanyl (meth)acrylate, behenyl (meth)acrylate, lignoceryl (meth)acrylate, ceryl (meth)acrylate, octacosyl (meth)acrylate, myrisyl (meth)acrylate, dotriacontane (meth)acrylate, etc.] and (meth)acrylic acid esters having a branched alkyl group having 18 to 36 carbon atoms [2-decyltetradecyl (meth)acrylate, etc.].
[0049] Among these, from the viewpoint of low temperature fixability, it is preferably at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 36 carbon atoms. More preferably, it is at least one selected from the group consisting of (meth)acrylic acid esters having a linear alkyl group having 18 to 30 carbon atoms. Even more preferably, it is at least one selected from the group consisting of linear stearyl (meth)acrylate and behenyl (meth)acrylate. The polymerizable monomer derived from the first monomer unit represented by the above formula (1) may be used alone or in combination of two or more kinds.
[0050] The SP value (J / cm) of the first monomer unit 3 ) 0.5 is SP1, SP1 is preferably less than 20.00, more preferably 19.00 or less, and even more preferably 18.40 or less. The lower limit is not particularly limited, but is preferably 17.00 or more.
[0051] It is preferable that the first resin has a second monomer unit represented by the following formula (2) or (3) which is different from the first monomer unit in the first resin.
[0052] [ka] (In the formula, X represents a single bond or an alkylene group having 1 to 6 carbon atoms, R 3 is a nitrile group (-C≡N), an amide group (-C(=O)NHR 10 (R 10 represents a hydrogen atom or an alkyl group having 1 to 4 carbon atoms. 31 (R 31 represents a hydrogen atom, an alkyl group having 1 to 6 carbon atoms, or a hydroxyalkyl group having 1 to 6 carbon atoms; Urea group (-NH-C(=O)-N(R 33 )2(R 33each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms; -COO(CH2)2NHCOOR 34 (R 34 represents an alkyl group having 1 to 4 carbon atoms; or -COO(CH2)2-NH-C(=O)-N(R 35 )2(R 35 each independently represents a hydrogen atom or an alkyl group having 1 to 6 carbon atoms. represents R 4 represents a hydrogen atom or a methyl group.
[0053] [ka] (In the formula, R 5 represents an alkyl group having 1 to 4 carbon atoms, R 6 represents a hydrogen atom or a methyl group.
[0054] The SP value of the second monomer unit is SP2 (J / cm 3 ) 0.5 When it is set as above, it is preferable to satisfy the following relational expression (4): It is more preferable to satisfy the following relational expression (4)'. 21.00(J / cm 3 ) 0.5 ≦SP2 (4) 25.00(J / cm 3 ) 0.5 ≦SP2···(4)'
[0055] When the SP2 of the second monomer unit satisfies the above formula (4) relative to the SP1 of the first monomer unit, the second monomer unit has high polarity, and a polarity difference occurs between the first and second monomer units. This polarity difference promotes crystallization of the first monomer unit, resulting in excellent low-temperature fixability. Specifically, the first monomer unit is incorporated into a crystalline resin, and the first monomer units aggregate with each other to exhibit crystallinity.
[0056] Usually, the crystallization of the first monomer unit is inhibited when other monomer units are incorporated, making it difficult for the first monomer unit to exhibit crystallinity as a crystalline resin. However, by setting the SP1 of the first monomer unit and the SP2 of the second monomer unit within the above-mentioned range, it is believed that the first monomer unit and the second monomer unit can form a clear phase-separated state in the first resin without being miscible with each other, and it is believed that the melting point can be easily maintained without reducing the crystallinity.
[0057] Specifically, as the second monomer unit, for example, among the polymerizable monomers listed below, a polymerizable monomer that satisfies the above formula (4) can be used.
[0058] Monomers having a nitrile group; for example, acrylonitrile, methacrylonitrile, etc.
[0059] Monomers having a hydroxy group; for example, 2-hydroxyethyl (meth)acrylate, 2-hydroxypropyl (meth)acrylate, and the like.
[0060] Monomers having an amide group: for example, acrylamide, monomers obtained by reacting an amine having 1 to 30 carbon atoms with a carboxylic acid having 2 to 30 carbon atoms and an ethylenically unsaturated bond (acrylic acid, methacrylic acid, etc.) by a known method.
[0061] Monomer having a urea group: for example, a monomer obtained by reacting an amine having 3 to 22 carbon atoms [primary amine (normal butylamine, t-butylamine, propylamine, isopropylamine, etc.), secondary amine (di-normal ethylamine, di-normal propylamine, di-normal butylamine, etc.), aniline, cycloxylamine, etc.] with an isocyanate having 2 to 30 carbon atoms and an ethylenically unsaturated bond by a known method, etc.
[0062] Monomers having a carboxy group; for example, methacrylic acid, acrylic acid, 2-carboxyethyl (meth)acrylate.
[0063] Among them, it is preferable to use a monomer having a nitrile group, an amide group, a hydroxy group, or a urea group. More preferably, it is a monomer having at least one functional group selected from the group consisting of a nitrile group, an amide group, a hydroxy group, and a urea group, and an ethylenically unsaturated bond. Acrylonitrile and methacrylonitrile are particularly preferable.
[0064] Also preferably used as the second monomer unit are vinyl esters such as vinyl acetate, vinyl propionate, vinyl butyrate, vinyl caproate, vinyl caprylate, vinyl caprate, vinyl laurate, vinyl myristate, vinyl palmitate, vinyl stearate, vinyl pivalate, and vinyl octylate. Among these, vinyl esters are preferred from the viewpoint of low-temperature fixability because they are non-conjugated monomers and therefore tend to maintain a suitable reactivity with the first polymerizable monomer and tend to increase the crystallinity of the polymer.
[0065] The proportion of the second monomer unit is preferably from 5.0% by mass to 40.0% by mass, and more preferably from 10.0% by mass to 30.0% by mass.
[0066] The copolymer may contain a third monomer unit derived from a third polymerizable monomer not included in the range of the above formula (4) (i.e., different from the first polymerizable monomer and the second polymerizable monomer) as long as the mass ratio of the first monomer unit and the second monomer unit described above is not impaired.
[0067] As the third polymerizable monomer, among the monomers exemplified as the second polymerizable monomer, a monomer not satisfying the above formula (4) can be used. For example, the following monomers can also be used. Styrene, o-methylstyrene and other styrene and derivatives thereof, (meth)acrylic acid esters such as methyl (meth)acrylate, n-butyl (meth)acrylate, t-butyl (meth)acrylate and 2-ethylhexyl (meth)acrylate. Among these, the third polymerizable monomer is preferably styrene from the viewpoint of charge diffusion.
[0068] The proportion of the third monomer unit is preferably 5.0% by mass or more and 50.0% by mass or less, and more preferably 10.0% by mass or more and 30.0% by mass or less.
[0069] <Second Resin> The binder resin contains a second resin, and the second resin is an amorphous resin. The second resin forming the domain may be a known amorphous resin, and is preferably a polyester resin, a styrene-acrylic resin, or a hybrid resin thereof from the viewpoints of low-temperature fixability and fixation separation property.
[0070] As the styrene-acrylic resin, a styrene-acrylic resin that is usually used in a toner can be suitably used.
[0071] Examples of styrene monomers include styrene, α-methylstyrene, β-methylstyrene, o-methylstyrene, m-methylstyrene, p-methylstyrene, 2,4-dimethylstyrene, pn-butylstyrene, p-tert-butylstyrene, pn-hexylstyrene, pn-octylstyrene, pn-nonylstyrene, pn-decylstyrene, pn-dodecylstyrene, p-methoxystyrene, and p-phenylstyrene. These styrene monomers can be used alone or in combination.
[0072] Examples of the (meth)acrylic monomer include methyl (meth)acrylate, ethyl (meth)acrylate, n-propyl (meth)acrylate, iso-propyl (meth)acrylate, n-butyl (meth)acrylate, iso-butyl (meth)acrylate, tert-butyl (meth)acrylate, n-amyl (meth)acrylate, n-hexyl (meth)acrylate, 2-ethylhexyl (meth)acrylate, n-octyl (meth)acrylate, n-nonyl (meth)acrylate, cyclohexyl (meth)acrylate, benzyl (meth)acrylate, dimethyl phosphate ethyl (meth)acrylate, diethyl phosphate ethyl (meth)acrylate, dibutyl phosphate ethyl (meth)acrylate, and 2-benzoyloxyethyl (meth)acrylate, (meth)acrylonitrile, 2-hydroxyethyl (meth)acrylate, (meth)acrylic acid, and maleic acid. These (meth)acrylic monomers can be used alone or in combination.
[0073] As the polyester resin, a polyester resin that is usually used in a toner can be suitably used. As a monomer used in the polyester resin, a polyhydric alcohol (a divalent or trivalent or higher alcohol), a polyvalent carboxylic acid (a divalent or trivalent or higher carboxylic acid), an acid anhydride thereof, or a lower alkyl ester thereof can be mentioned.
[0074] The polyhydric alcohols include the following:
[0075] Examples of dihydric alcohols include the following bisphenol derivatives: polyoxypropylene(2.2)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(3.3)-2,2-bis(4-hydroxyphenyl)propane, polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(2.0)-polyoxyethylene(2.0)-2,2-bis(4-hydroxyphenyl)propane, polyoxypropylene(6)-2,2-bis(4-hydroxyphenyl)propane, etc.
[0076] Other polyhydric alcohols include ethylene glycol, diethylene glycol, triethylene glycol, 1,2-propanediol, 1,3-propanediol, 1,4-butanediol, neopentyl glycol, 1,4-butenediol, 1,5-pentanediol, 1,6-hexanediol, 1,4-cyclohexanedimethanol, dipropylene glycol, polyethylene glycol, polypropylene glycol, polytetramethylene glycol, sorbitol, 1,2,3,6-hexanetetrol, 1,4-sorbitan, pentaerythritol, dipentaerythritol, tripentaerythritol, 1,2,4-butanetriol, 1,2,5-pentanetriol, glycerin, 2-methylpropanetriol, 2-methyl-1,2,4-butanetriol, trimethylolethane, trimethylolpropane, and 1,3,5-trihydroxymethylbenzene.
[0077] These polyhydric alcohols can be used alone or in combination.
[0078] Examples of the polycarboxylic acid include the following.
[0079] Examples of divalent carboxylic acids include maleic acid, fumaric acid, citraconic acid, itaconic acid, glutaconic acid, phthalic acid, isophthalic acid, terephthalic acid, succinic acid, adipic acid, sebacic acid, azelaic acid, malonic acid, n-dodecenylsuccinic acid, isododecenylsuccinic acid, n-dodecylsuccinic acid, isododecylsuccinic acid, n-octenylsuccinic acid, n-octylsuccinic acid, isooctylsuccinic acid, isooctylsuccinic acid, anhydrides of these acids, and lower alkyl esters thereof. Of these, maleic acid, fumaric acid, terephthalic acid, and n-dodecenylsuccinic acid are preferably used.
[0080] Examples of trivalent or higher carboxylic acids, their acid anhydrides, and their lower alkyl esters include the following.
[0081] 1,2,4-benzenetricarboxylic acid (trimellitic acid), 2,5,7-naphthalenetricarboxylic acid, 1,2,4-naphthalenetricarboxylic acid, 1,2,4-butanetricarboxylic acid, 1,2,5-hexanetricarboxylic acid, 1,3-dicarboxyl-2-methyl-2-methylenecarboxypropane, 1,2,4-cyclohexanetricarboxylic acid, tetra(methylenecarboxyl)methane, 1,2,7,8-octanetetracarboxylic acid, pyromellitic acid, empol trimer acid, acid anhydrides thereof, or lower alkyl esters thereof. Among these, 1,2,4-benzenetricarboxylic acid (trimellitic acid) or its derivatives such as an acid anhydride are preferably used because they are inexpensive and the reaction can be easily controlled.
[0082] These polyvalent carboxylic acids can be used alone or in combination.
[0083] In addition, it is preferable that the first resin contains a resin containing a nitrile group and the second resin contains a resin containing a nitrile group, from the viewpoint of enabling control of compatibility, for example, by bringing the polarities closer to each other to enhance the compatibility between the first resin and the second resin.
[0084] <Other resins> The binder resin may contain a resin other than the first resin and the second resin to the extent that the effect of the present disclosure is not impaired for the purpose of improving pigment dispersibility, etc. Examples of such resins include the following.
[0085] Polyvinyl chloride, phenolic resin, natural resin modified phenolic resin, natural resin modified maleic acid resin, polyvinyl acetate, silicone resin, polyester resin, polyurethane resin, polyamide resin, furan resin, epoxy resin, xylene resin, polyvinyl butyral, terpene resin, coumarone-indene resin, petroleum-based resin.
[0086] <Release agent (wax)> The toner particles of the present invention may contain a release agent, if necessary. Examples of the release agent include the following.
[0087] Hydrocarbon waxes such as microcrystalline wax, paraffin wax, and Fischer-Tropsch wax; oxides of hydrocarbon waxes such as oxidized polyethylene wax or block copolymers thereof; waxes whose main component is fatty acid esters such as carnauba wax; and partially or completely deoxidized fatty acid esters such as deoxidized carnauba wax.
[0088] Further examples include the following: saturated straight-chain fatty acids such as palmitic acid, stearic acid, and montanic acid; unsaturated fatty acids such as brassidic acid, eleostearic acid, and parinaric acid; saturated alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; polyhydric alcohols such as sorbitol; esters of fatty acids such as palmitic acid, stearic acid, behenic acid, and montanic acid with alcohols such as stearyl alcohol, aralkyl alcohol, behenyl alcohol, carnaubyl alcohol, ceryl alcohol, and melissyl alcohol; fatty acid amides such as linoleic acid amide, oleic acid amide, and lauric acid amide; methylene bisstearic acid amide, ethylene biscapric acid amide, ethylene bislauric acid amide, hexamethylene saturated fatty acid bisamides such as ethylene bisoleamide, hexamethylene bisoleamide, N,N'-dioleyl adipamide, N,N'-dioleyl sebacamide; aromatic bisamides such as m-xylene bisstearyl isophthalamide; fatty metal salts (commonly known as metal soaps) such as calcium stearate, calcium laurate, zinc stearate, and magnesium stearate; waxes grafted onto aliphatic hydrocarbon waxes using vinyl monomers such as styrene and acrylic acid; partial esters of fatty acids and polyhydric alcohols such as behenic acid monoglyceride; and methyl ester compounds having hydroxy groups obtained by hydrogenation of vegetable oils and fats.
[0089] The content of the wax is preferably 2.0 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the binder resin.
[0090] <Coloring agent> The toner particles of the present invention may contain a colorant, if necessary. Examples of the colorant include the following.
[0091] Examples of black colorants include carbon black, and a mixture of a yellow colorant, a magenta colorant, and a cyan colorant toned to black. As the colorant, a pigment may be used alone, but it is more preferable to use a dye and a pigment in combination to improve the clarity of the colorant from the viewpoint of the image quality of a full-color image.
[0092] Magenta toner pigments include the following: CI Pigment Red 1, 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, 13, 14, 15, 16, 17, 18, 19, 21, 22, 23, 30, 31, 32, 37, 38, 39, 40, 41, 48:2, 48:3, 48:4, 49, 50, 51, 52, 53, 54, 55, 57:1, 58, 60, 63, 64, 68, 81:1, 83, 87, 88, 89, 90, 112, 114, 122, 123, 146, 147, 150, 163, 184, 202, 206, 207, 209, 238, 269, 282; CI Pigment Violet 19; CI Bat Red 1, 2, 10, 13, 15, 23, 29, 35.
[0093] Dyes for magenta toners include solvent dyes such as CI Solvent Red 1, 3, 8, 23, 24, 25, 27, 30, 49, 81, 82, 83, 84, 100, 109, 121; CI Disperse Red 9; CI Solvent Violet 8, 13, 14, 21, 27; CI Disperse Violet 1; basic dyes such as CI Basic Red 1, 2, 9, 12, 13, 14, 15, 17, 18, 22, 23, 24, 27, 29, 32, 34, 35, 36, 37, 38, 39, 40; and CI Basic Violet 1, 3, 7, 10, 14, 15, 21, 25, 26, 27, 28.
[0094] Pigments for cyan toners include the following: CI Pigment Blue 2, 3, 15:2, 15:3, 15:4, 16, 17; CI Vat Blue 6; CI Acid Blue 45; copper phthalocyanine pigments having 1 to 5 phthalimidomethyl groups substituted on the phthalocyanine skeleton.
[0095] Cyan toner dyes include CI Solvent Blue 70.
[0096] Yellow toner pigments include: CI Pigment Yellow 1, 2, 3, 4, 5, 6, 7, 10, 11, 12, 13, 14, 15, 16, 17, 23, 62, 65, 73, 74, 83, 93, 94, 95, 97, 109, 110, 111, 120, 127, 128, 129, 147, 151, 154, 155, 168, 174, 175, 176, 180, 181, 185; CI Vat Yellow 1, 3, 20. Yellow toner dyes include CI Solvent Yellow 162.
[0097] These colorants can be used alone or in combination, or in the form of a solid solution. The colorant is selected in consideration of hue angle, chroma, brightness, light resistance, OHP transparency, and dispersibility in toner.
[0098] The content of the colorant is preferably 0.1 parts by mass or more and 30.0 parts by mass or less with respect to 100 parts by mass of the total amount of the resin components.
[0099] <Charge control agent> The toner particles of the present invention may contain a charge control agent, if necessary. By blending a charge control agent, the charge characteristics can be stabilized and the amount of triboelectric charge can be optimally controlled according to the development system.
[0100] As the charge control agent, known substances can be used, but particularly preferred are metal compounds of aromatic carboxylic acids, which are colorless, can charge the toner quickly, and can stably maintain a constant charge amount.
[0101] Examples of negative charge control agents include metal salicylate compounds, metal naphthoate compounds, metal dicarboxylate compounds, polymeric compounds having sulfonic acid or carboxylic acid on the side chain, polymeric compounds having sulfonate or sulfonate ester on the side chain, polymeric compounds having carboxylate or carboxylate ester on the side chain, boron compounds, urea compounds, silicon compounds, and calixarenes.
[0102] The charge control agent may be added internally or externally to the toner particles. The content of the charge control agent is preferably 0.2 parts by mass to 10.0 parts by mass, more preferably 0.5 parts by mass to 10.0 parts by mass, based on 100 parts by mass of the binder resin.
[0103] <Inorganic fine particles> The toner of the present invention may contain inorganic fine particles as required. The inorganic fine particles may be added internally to the toner particles, or may be mixed with the toner as an external additive.
[0104] Examples of inorganic fine particles include silica fine particles, titanium oxide fine particles, alumina fine particles, and double oxide fine particles thereof. Among inorganic fine particles, silica fine particles and titanium oxide fine particles are preferred for improving flowability and uniform charging.
[0105] The inorganic fine particles are preferably hydrophobized with a hydrophobizing agent such as a silane compound, silicone oil, or a mixture thereof.
[0106] From the viewpoint of improving fluidity, inorganic fine particles as external additives should have a specific surface area of 50 m 2 / g or more 400m 2 From the viewpoint of improving durability and stability, the inorganic fine particles as the external additive preferably have a specific surface area of 10 m 2 / g or more 50m 2 In order to achieve both improved fluidity and durability and stability, inorganic fine particles having a specific surface area within the above range may be used in combination.
[0107] The content of the external additive is preferably 0.1 parts by mass or more and 10.0 parts by mass or less with respect to 100 parts by mass of the toner particles. The toner particles and the external additive can be mixed using a known mixer such as a Henschel mixer.
[0108] <Developer> The toner of the present invention can be used as a one-component developer, but is more preferably mixed with a magnetic carrier and used as a two-component developer in that stable images can be obtained over a long period of time.
[0109] Examples of magnetic carriers that can be used include generally known magnetic carriers such as iron powder with an oxidized surface, unoxidized iron powder, metal particles such as iron, lithium, calcium, magnesium, nickel, copper, zinc, cobalt, manganese, and rare earth elements, alloy particles thereof, oxide particles, magnetic materials such as ferrite, and magnetic material-dispersed resin carriers (so-called resin carriers) that contain a magnetic material and a binder resin that holds the magnetic material in a dispersed state.
[0110] When the toner of the present invention is mixed with a magnetic carrier to be used as a two-component developer, good results are usually obtained when the carrier mixing ratio in terms of the toner concentration in the two-component developer is preferably 2.0% by mass or more and 15.0% by mass or less, more preferably 4.0% by mass or more and 13.0% by mass or less.
[0111] <Toner manufacturing method> The method for producing the toner of the present invention is not particularly limited, and known methods such as a pulverization method, a suspension polymerization method, a dissolution suspension method, an emulsion aggregation method, and a dispersion polymerization method can be used.
[0112] Grinding method: The procedure for producing the toner by the pulverization method will be described below.
[0113] <Raw material mixing process> In the raw material mixing process, materials constituting the toner particles, such as binder resin, wax, colorant, and other components such as charge control agent as necessary, are weighed out in predetermined amounts, blended, and mixed. Examples of mixing devices include a double cone mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, and a Mechano Hybrid (manufactured by Nippon Coke and Engineering Co., Ltd.).
[0114] <Melting and kneading process> Next, the mixed materials are melt-kneaded to disperse the wax in the binder resin. In the melt-kneading process, a batch-type kneader such as a pressure kneader or a Banbury mixer, or a continuous kneader can be used, and single-screw or twin-screw extruders are mainstream due to their advantage of continuous production. For example, a KTK twin-screw extruder (manufactured by Kobe Steel, Ltd.), a TEM twin-screw extruder (manufactured by Toshiba Machine Co., Ltd.), a PCM kneader (manufactured by Ikegai Iron Works Co., Ltd.), a twin-screw extruder (manufactured by KCK Corporation), a Co-kneader (manufactured by Buss Co., Ltd.), and Kneadex (manufactured by Nippon Coke and Engineering Co., Ltd.) can be mentioned. Furthermore, the resin composition obtained by melt-kneading may be rolled with a two-roller or the like, and cooled with water or the like in a cooling process.
[0115] The state of dispersion of the first resin and the second resin, the number-average diameter of the domains, and the like can be controlled by adjusting the kneading temperature in the melt-kneading step, the number of revolutions of the screw, and the like.
[0116] <Crushing process> The cooled resin composition is then pulverized to a desired particle size in a pulverization process, which involves coarse pulverization using a pulverizer such as a crusher, hammer mill, or feather mill, followed by further pulverization using a pulverizer such as a Cryptron System (Kawasaki Heavy Industries), a Super Rotor (Nisshin Engineering), a Turbo Mill (Turbo Kogyo), or an air jet type pulverizer.
[0117] <Classification process> Thereafter, as necessary, the mixture is classified using a classifier or sieve such as an inertial classification type Elbow Jet (manufactured by Nittetsu Mining Co., Ltd.), a centrifugal classification type Turboplex (manufactured by Hosokawa Micron Corporation), a TSP Separator (manufactured by Hosokawa Micron Corporation), or a Faculty (manufactured by Hosokawa Micron Corporation).
[0118] <Surface treatment process> Thereafter, it is preferable to perform a surface treatment of the toner particles by heating. For example, the surface treatment can be performed by using a surface treatment device shown in FIG.
[0119] The mixture supplied by the material supply means 31 is introduced into an introduction pipe 33, which is installed vertically to the material supply means, by compressed gas adjusted by a compressed gas adjustment means 32. The mixture passing through the introduction pipe is uniformly dispersed by a conical protruding member 4 installed in the center of the material supply means, and is introduced into eight supply pipes 35 that radiate outward, and then into a treatment chamber 6 where heat treatment is carried out.
[0120] At this time, the flow of the mixture supplied to the treatment chamber is regulated by a regulating means 39 for regulating the flow of the mixture provided in the treatment chamber, so that the mixture supplied to the treatment chamber is heat-treated while swirling in the treatment chamber, and then cooled.
[0121] Hot air for heat-treating the supplied mixture is supplied from hot air supplying means 37, and is introduced into the treatment chamber by spirally swirling the hot air using a swirling member 43 for swirling the hot air. The configuration is such that the swirling member 43 for swirling the hot air has a plurality of blades, and the swirling of the hot air can be controlled by the number and angle of the blades. The hot air supplied into the treatment chamber preferably has a temperature of 100°C to 300°C at the outlet of the hot air supplying means 37. If the temperature at the outlet of the hot air supplying means is within the above range, it is possible to uniformly spheronize the toner particles while preventing the toner particles from fusing or coalescing due to excessive heating of the mixture.
[0122] The heat-treated toner particles are then cooled by cold air supplied from cold air supply means 38, and the temperature of the cold air supplied from cold air supply means 38 is preferably -20°C to 30°C. If the temperature of the cold air is within the above range, the heat-treated toner particles can be efficiently cooled, and the fusion and coalescence of the heat-treated toner particles can be prevented without impeding the uniform spheroidization of the mixture. The absolute moisture content of the cold air is 0.5 g / m 3 More than 15.0g / m 3 It is preferable that:
[0123] Next, the cooled heat-treated toner particles are collected by the collecting means 40 at the bottom end of the processing chamber. A blower (not shown) is provided ahead of the collecting means, so that the toner particles are sucked and transported by the blower.
[0124] The powder particle supply port 44 is provided so that the swirling direction of the supplied mixture and the swirling direction of the hot air are the same, and the recovery means 40 of the surface treatment device is provided on the outer periphery of the treatment chamber so as to maintain the swirling direction of the swirled powder particles. Furthermore, the cold air supplied from the cold air supply means 38 is configured to be supplied from the outer periphery of the device to the circumferential surface inside the treatment chamber in a horizontal and tangential direction. The swirling direction of the toner supplied from the powder supply port, the swirling direction of the cold air supplied from the cold air supply means, and the swirling direction of the hot air supplied from the hot air supply means are all the same. Therefore, no turbulence occurs in the treatment chamber, the swirling flow in the device is strengthened, a strong centrifugal force is applied to the toner, and the dispersibility of the toner is further improved, so that a toner with a uniform shape and few coalesced particles can be obtained.
[0125] <External addition process> Furthermore, if necessary, an external additive is added to the surface of the toner particles. As a method for adding an external additive, a method is mentioned in which a predetermined amount of a classified toner and various known external additives are mixed, and stirred and mixed using a mixing device such as a double con mixer, a V-type mixer, a drum type mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation) as an external additive machine.
[0126] Emulsion aggregation method: Next, the production of toner particles by the emulsion aggregation method will be described.
[0127] In the emulsion aggregation method, toner particles are manufactured through a dispersion process in which a fine particle dispersion liquid made of the constituent materials of the toner particles is prepared, an aggregation process in which fine particles made of the constituent materials of the toner particles are aggregated and the particle size is controlled until the particle size becomes the same as that of the toner particles, a fusion process in which the resin contained in the obtained aggregated particles is fused, a subsequent cooling process, a metal removal process in which the obtained toner is filtered and excess polyvalent metal ions are removed, a filtration / washing process in which the toner particles are washed with ion-exchanged water or the like, and a process in which moisture is removed from the washed toner particles and they are dried.
[0128] <Step of preparing a resin particle dispersion (dispersion step)> The resin microparticle dispersion liquid can be prepared by a known method, but is not limited to these methods.The known methods include, for example, emulsion polymerization method, self-emulsification method, phase inversion emulsification method in which resin is emulsified by adding aqueous medium to the resin solution dissolved in organic solvent, and forced emulsification method in which resin is forcedly emulsified by high temperature treatment in aqueous medium without using organic solvent.
[0129] Specifically, the first resin and the second resin are dissolved in an organic solvent capable of dissolving them, and a surfactant or a basic compound is added as necessary. In this case, if the resin is a crystalline resin having a melting point, it may be dissolved by heating to above the melting point. Next, while stirring with a homogenizer or the like, an aqueous medium is slowly added to precipitate the resin fine particles. Thereafter, the solvent is removed by heating or reducing pressure to prepare an aqueous dispersion of the resin fine particles.
[0130] As the organic solvent used to dissolve the resin, any organic solvent that can dissolve the resin can be used, but it is preferable to use an organic solvent that forms a homogeneous phase with water, such as toluene, from the viewpoint of suppressing the generation of coarse powder.
[0131] The surfactant is not particularly limited, and examples thereof include anionic surfactants such as sulfate salts, sulfonates, carboxylates, phosphates, and soaps, cationic surfactants such as amine salts and quaternary ammonium salts, and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols. The surfactants may be used alone or in combination of two or more.
[0132] Examples of the basic compound include inorganic bases such as sodium hydroxide and potassium hydroxide, and organic bases such as ammonia, triethylamine, trimethylamine, dimethylaminoethanol, and diethylaminoethanol. The basic compound may be used alone or in combination of two or more kinds.
[0133] The 50% particle size (D50) based on volume distribution of the resin fine particles in the aqueous dispersion of the resin fine particles is preferably about 0.05 μm to 1.00 μm, more preferably about 0.05 μm to 0.40 μm. By adjusting the 50% particle size (D50) based on volume distribution to the above range, it becomes easy to obtain toner particles with a weight average particle size of 3 μm to 10 μm, which is appropriate for toner particles.
[0134] In addition, the 50% particle size (D50) based on volume distribution can be measured using a dynamic light scattering particle size distribution meter Nanotrac UPA-EX150 (manufactured by Nikkiso).
[0135] <Preparation of colorant particle dispersion> The colorant particle dispersion liquid can be prepared by the following known methods, but is not limited to these methods.
[0136] The colorant, the aqueous medium, and the dispersant can be mixed by a known mixer such as a stirrer, an emulsifier, or a disperser. The dispersant used here can be a known one such as a surfactant or a polymer dispersant.
[0137] Although both the surfactant and the polymer dispersant can be removed in the washing step described below, the surfactant is preferred from the viewpoint of washing efficiency.
[0138] Examples of surfactants include anionic surfactants such as sulfate ester salts, sulfonate salts, phosphate esters, and soap-based surfactants; cationic surfactants such as amine salts and quaternary ammonium salts; and nonionic surfactants such as polyethylene glycols, alkylphenol ethylene oxide adducts, and polyhydric alcohols.
[0139] Among these, nonionic surfactants or anionic surfactants are preferred. A nonionic surfactant and an anionic surfactant may be used in combination. The surfactant may be used alone or in combination of two or more. The concentration of the surfactant in the aqueous medium is preferably about 0.5% by mass or more and 5% by mass or less.
[0140] The content of the colorant particles in the colorant particle dispersion is not particularly limited, but is preferably from 1% by mass to 30% by mass with respect to the total mass of the colorant particle dispersion.
[0141] From the viewpoint of dispersibility of the colorant in the toner particles finally obtained, the dispersed particle size of the colorant particles in the aqueous dispersion of the colorant is preferably 0.50 μm or less in terms of the 50% particle size (D50) based on the volume distribution. For the same reason, it is preferable that the 90% particle size (D90) based on the volume distribution is 2 μm or less. The 50% particle size (D50) based on the volume distribution of the colorant particles dispersed in the aqueous medium may be measured using a dynamic light scattering particle size distribution meter (Nanotrac UPA-EX150: manufactured by Nikkiso).
[0142] Known mixers such as stirrers, emulsifiers, and dispersers used when dispersing a colorant in an aqueous medium include ultrasonic homogenizers, jet mills, pressure homogenizers, colloid mills, ball mills, sand mills, and paint shakers. These may be used alone or in combination.
[0143] <Preparation of Wax Microparticle Dispersion> The wax particle dispersion can be prepared by the following known methods, but is not limited to these methods.
[0144] Wax microparticle dispersions can be produced by adding wax to an aqueous medium containing a surfactant, heating it to above the melting point of the wax, dispersing it into particles using a homogenizer with strong shearing capabilities (e.g., M Technique's "Clearmix W Motion") or a pressure-discharge type disperser (e.g., Gaulin Homogenizer) and then cooling it below the melting point.
[0145] The particle size of the dispersed wax particles in the aqueous wax dispersion is preferably 0.03 μm to 1.0 μm, more preferably 0.10 μm to 0.50 μm, in terms of the 50% particle size (D50) based on volume distribution. It is also preferable that no coarse particles of 1 μm or more exist.
[0146] By having the dispersed particle size of the wax microparticle dispersion within the above range, it becomes possible to have the wax finely dispersed in the toner particles, which maximizes the exudation effect during fixing and makes it possible to obtain good separation properties. The 50% particle size (D50) based on the volume distribution of the wax microparticle dispersion dispersed in the aqueous medium can be measured using a dynamic light scattering particle size distribution meter (Nanotrac UPA-EX150: manufactured by Nikkiso).
[0147] <Mixing process> In the mixing step, a mixed liquid is prepared by mixing the first resin particle dispersion liquid, the second resin particle dispersion liquid, and, if necessary, the wax particle dispersion liquid and the colorant particle dispersion liquid, etc. This may be carried out using a known mixing device such as a homogenizer or a mixer.
[0148] <Step of forming aggregate particles (aggregation step)> In the aggregating step, the fine particles contained in the mixed liquid prepared in the mixing step are aggregated to form aggregates having a desired particle size. At this time, an aggregating agent is added and mixed as necessary, and at least one of heating and mechanical power is appropriately applied to form aggregates in which the resin fine particles and, as necessary, the wax fine particles and the colorant fine particles are aggregated.
[0149] As the flocculant, a flocculant containing a divalent or higher metal ion may be used as necessary.
[0150] The flocculants containing divalent or higher metal ions have high flocculation power and can achieve the purpose by adding a small amount. These flocculants can also ionically neutralize the ionic surfactants contained in the resin particle dispersion, the wax particle dispersion, and the colorant particle dispersion.
[0151] As a result, due to the effects of salting out and ionic crosslinking, the resin particles, wax particles, and colorant particles tend to aggregate.
[0152] In the aggregation step, if necessary, a new resin particle dispersion may be added after the aggregates are formed. By adding a new resin particle dispersion and aggregating the aggregates, a core-shell structure can be realized.
[0153] The aggregation process is a process for forming aggregates of the toner particle size in an aqueous medium. The weight average particle size of the aggregates produced in the aggregation process is preferably 3 μm or more and 10 μm or less. The weight average particle size may be measured using a particle size distribution analyzer (Coulter Multisizer III, manufactured by Coulter) using the Coulter method.
[0154] <Fusion process> In the fusion step, an aggregation terminator may be added to the dispersion containing the aggregates obtained in the aggregation step under stirring in the same manner as in the aggregation step. Examples of the aggregation terminator include a basic compound that shifts the equilibrium of the acidic polar group of the surfactant to the dissociation side and stabilizes the aggregated particles. In addition, examples of the aggregation terminator include a chelating agent that partially dissociates the ionic bridge between the acidic polar group of the surfactant and the metal ion serving as the aggregating agent, and forms a coordinate bond with the metal ion to stabilize the aggregated particles.
[0155] After the dispersion state of the aggregated particles in the dispersion liquid has become stable due to the action of the aggregation terminator, the aggregated particles may be fused by heating to a temperature equal to or higher than the glass transition temperature or melting point of the resin.
[0156] It is also possible to control the number-average diameter of the domains by adjusting the temperature during fusion. The weight-average particle diameter of the obtained toner particles is preferably about 3 μm or more and 10 μm or less.
[0157] <Filtration process, washing process, drying process, classification process> Thereafter, a filtration step for filtering out the solid content of the toner particles, and if necessary, a washing step, a drying step, and a classification step for adjusting the particle size are carried out to obtain toner particles.
[0158] The obtained toner particles may be used as a toner as it is. The obtained toner particles may be mixed with inorganic fine particles and, if necessary, other external additives to obtain a toner. The toner particles, inorganic fine particles, and other external additives may be mixed using a mixing device such as a double con mixer, a V-type mixer, a drum mixer, a super mixer, a Henschel mixer, a Nauta mixer, a Mechano Hybrid (manufactured by Nippon Coke & Engineering Co., Ltd.), or a Nobilta (manufactured by Hosokawa Micron Corporation).
[0159] The methods for measuring various physical properties of the toner particles and raw materials will be described below.
[0160] <Cross-section observation of toner (matrix domain structure, crystallinity ratio (area ratio of matrix), number-average circle-equivalent diameter of domain, average circularity)> First, a thin section is prepared as a reference sample for the abundance.
[0161] The first resin, which is a crystalline resin, is thoroughly dispersed in a visible light curable resin (Aronix LCR Series D800), and then irradiated with short wavelength light to cure. The resulting cured product is cut with an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin flake sample. In the same manner, a thin flake sample is also prepared for the second resin, which is an amorphous resin.
[0162] In addition, the first resin and the second resin are mixed at ratios of 0 / 100, 30 / 70, 70 / 30, and 100 / 0 by mass, and melt-kneaded to prepare kneaded products. These are also similarly dispersed in a visible light curable resin, cured, and then cut out to prepare thin flake samples.
[0163] Next, the cross sections of the cut samples are observed using a transmission electron microscope (JEM-2800, manufactured by JEOL Ltd.) (TEM-EDX), and element mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen. The mapping conditions are as follows: Accelerating voltage: 200 kV Electron beam irradiation size: 1.5 nm Live time limit: 600sec Dead time: 20~30 Mapping resolution: 256×256
[0164] Based on the spectral intensity (average in an area of 10 nm square) of each element, calculate (oxygen element intensity / carbon element intensity) and (nitrogen element intensity / carbon element intensity) and create a calibration curve for the mass ratio of the first resin to the second resin. If the monomer unit of the first resin contains nitrogen atoms, the calibration curve of (nitrogen element intensity / carbon element intensity) will be used for future quantification.
[0165] The toner samples are then analyzed.
[0166] After thoroughly dispersing the toner in a visible light curable resin (Aronix LCR Series D800), it is irradiated with short wavelength light to cure. The resulting cured product is cut with an ultramicrotome equipped with a diamond knife to prepare a 250 nm thin sample.
[0167] Next, the cut sample is observed using a transmission electron microscope (JEM-2800, manufactured by JEOL Ltd.) (TEM-EDX). A cross-sectional image of the toner particle is obtained, and element mapping is performed using EDX. The elements to be mapped are carbon, oxygen, and nitrogen.
[0168] The toner cross section to be observed is selected as follows: First, the cross-sectional area of the toner is calculated from the toner cross-sectional image, and the diameter of a circle having the same area as that cross-sectional area (equivalent circle diameter) is calculated. Only toner cross-sectional images in which the absolute value of the difference between this equivalent circle diameter and the weight-average particle diameter (D4) of the toner is within 1.0 μm are observed.
[0169] For the domains confirmed by the observed image, the (oxygen element intensity / carbon element intensity) and / or (nitrogen element intensity / carbon element intensity) are calculated based on the (average of 10 nm square) spectral intensity of each element, and the ratio of the first resin to the second resin is calculated by comparing with the calibration curve. The domains in which the ratio of the second resin is 80% or more are defined as the domains of the present disclosure.
[0170] After identifying the domains confirmed by the observed image, the particle size of the domains present in the toner cross-sectional image is obtained by binarization processing. The particle size is the circle-equivalent diameter of the domain. This is measured at 10 points per toner, and the arithmetic average of the domain particle sizes of the 10 toner particles is taken as the "circle-equivalent number-average diameter" (nm).
[0171] Meanwhile, the area of the domains is calculated by adding up the areas of all the domains present in one toner cross-sectional image and designating this total area as S1. This is measured at 10 points per toner particle, and the total area of the domains of the 10 toner particles (i.e., S1 + S2... + S100) is calculated, and the arithmetic average value is designated as the "domain area."
[0172] For the toner cross-sectional area, the total cross-sectional areas of the toner (10 points per toner and 10 toner particles) obtained from the toner cross-sectional images used to obtain the domain area are calculated, and the arithmetic average value is taken as the "toner cross-sectional area." [Domain area] / [Toner cross-sectional area] x 100 is taken as the ratio of the domain area to the toner cross-sectional area (domain area ratio (%)), and 100 - this ratio is the "matrix area ratio (%)."
[0173] The "domain circularity" is estimated for each domain of area S1 to S100 in the cross-sectional image. The perimeter of the domain with area S1 is L1, and it is calculated using the formula: circularity 1 = (4π*(S1) / (L1)2). The "average circularity" is the average of the circularity degrees 1 to 100 thus calculated, and the "standard deviation of the domain circularity" is the standard deviation of the circularity degrees 1 to 100.
[0174] The binarization process and the calculation of the number-average diameter are carried out using Image Pro PLUS (manufactured by Nippon Roper Co., Ltd.).
[0175] <Method of separating each material from toner> By utilizing the difference in solubility of each material contained in the toner in a solvent, each material can be separated from the toner. First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin) is separated from the insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.). Second separation: The insoluble matter obtained in the first separation (first resin, wax, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated. Third separation: The soluble fraction (first resin, wax) obtained in the second separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (wax) are separated.
[0176] (When a third resin is included) First separation: The toner is dissolved in methyl ethyl ketone (MEK) at 23° C., and the soluble matter (second resin, third resin) is separated from the insoluble matter (first resin, wax, colorant, inorganic fine particles, etc.). Second separation: The soluble fraction (second resin, third resin) obtained in the first separation is dissolved in toluene at 23° C., and the soluble fraction (third resin) is separated from the insoluble fraction (second resin). Third separation: The insoluble matter obtained in the first separation (first resin, wax, colorant, inorganic fine particles, etc.) is dissolved in MEK at 100°C, and the soluble matter (first resin, wax) and the insoluble matter (colorant, inorganic fine particles, etc.) are separated. Fourth separation: The soluble fraction (first resin, wax) obtained in the third separation is dissolved in chloroform at 23° C., and the soluble fraction (first resin) and the insoluble fraction (wax) are separated.
[0177] (Measurement of the Contents of the First Resin and the Second Resin in the Binder Resin in the Toner) In each of the separation steps, the masses of the soluble and insoluble components are measured to calculate the contents of the first resin and the second resin in the binder resin in the toner.
[0178] <Method for measuring weight average molecular weight (Mw) of resins, etc. using gel permeation chromatography (GPC)> The weight average molecular weight (Mw) of a tetrahydrofuran (THF) soluble matter such as a resin is measured by gel permeation chromatography (GPC) as follows.
[0179] First, the resin is dissolved in tetrahydrofuran (THF) at room temperature for 24 hours. The resulting solution is then filtered through a solvent-resistant membrane filter "Myshoridisc" (manufactured by Tosoh Corporation) with a pore size of 0.2 μm to obtain a sample solution. The sample solution is adjusted so that the concentration of components soluble in THF is approximately 0.8 mass%. This sample solution is used to perform measurements under the following conditions. Equipment: HLC8120 GPC (detector: RI) (Tosoh Corporation) Column: Shodex KF-801, 802, 803, 804, 805, 806, 807 (Showa Denko) Eluent: tetrahydrofuran (THF) Flow rate: 1.0mL / min Oven temperature: 40.0℃ Sample injection volume: 0.10 mL
[0180] In calculating the molecular weight of the sample, a molecular weight calibration curve prepared using standard polystyrene resins (product names: "TSK Standard Polystyrene F-850, F-450, F-288, F-128, F-80, F-40, F-20, F-10, F-4, F-2, F-1, A-5000, A-2500, A-1000, A-500", manufactured by Tosoh Corporation) is used.
[0181] <Measuring method of melting point, endothermic peak and endothermic amount of toner, resin, etc.> The melting points of the toner and resin, as well as the endothermic peak and endothermic amount, are measured using a DSC Q1000 (manufactured by TA Instruments) under the following conditions. Heating rate: 10℃ / min Measurement start temperature: 20℃ End of measurement temperature: 180℃
[0182] The melting points of indium and zinc are used to correct the temperature of the detector, and the heat quantity is corrected using the heat of fusion of indium.
[0183] Specifically, about 5 mg of a sample is weighed out and placed in an aluminum pan, and differential scanning calorimetry is performed using an empty silver pan as a reference.
[0184] The peak temperature of the maximum endothermic peak in the first temperature rise process is taken as the melting point. Here, the maximum endothermic peak is the peak with the largest amount of endothermic heat when there are multiple peaks. Furthermore, the amount of endothermic heat of the maximum endothermic peak is calculated.
[0185] <Method of measuring resin softening point (Tm)> The softening point of the resin is measured using a constant load extrusion type capillary rheometer "Flow characteristic evaluation device Flow Tester CFT-500D" (Shimadzu Corporation) according to the manual that comes with the device. With this device, a constant load is applied from above the measurement sample by a piston while the measurement sample filled in a cylinder is heated and melted, and the molten measurement sample is extruded from the die at the bottom of the cylinder, and a flow curve showing the relationship between the piston descent amount and temperature can be obtained.
[0186] The softening point is the "melting temperature in the 1 / 2 method" described in the manual attached to the "Flow property evaluation device Flow Tester CFT-500D." The melting temperature in the 1 / 2 method is calculated as follows.
[0187] First, calculate half the difference between the amount of piston descent when the outflow ends (end of outflow, Smax) and the amount of piston descent when the outflow starts (minimum point, Smin) (this is X. X=(Smax-Smin) / 2). Then, the temperature of the flow curve when the amount of piston descent is the sum of X and Smin is the melting temperature in the 1 / 2 method.
[0188] The measurement sample is prepared by compressing approximately 1.0 g of resin at approximately 10 MPa for approximately 60 seconds using a tablet molding machine (e.g., NT-100H, manufactured by NPA Systems) in an environment of 25°C to form a cylindrical shape with a diameter of approximately 8 mm.
[0189] The specific operations for the measurement are performed according to the manual that comes with the device.
[0190] The measurement conditions for the CFT-500D are as follows. Test mode: Temperature rise method Starting temperature: 50℃ Achieved temperature: 200℃ Measurement interval: 1.0℃ Heating rate: 4.0℃ / min Piston cross-sectional area: 1.000cm 2 Test load (piston load): 10.0kgf (0.9807MPa) Preheat time: 300 seconds Die hole diameter: 1.0mm Die length: 1.0mm
[0191] <Method of measuring weight-average particle size (D4) of toner (particles)> The weight average particle size (D4) of the toner (particles) is measured with an effective measurement channel count of 25,000 channels using a precision particle size distribution measuring device equipped with a 100 μm aperture tube and a fine hole electrical resistance method called "Coulter Counter Multisizer 3" (registered trademark, manufactured by Beckman Coulter, Inc.) and the accompanying dedicated software "Beckman Coulter Multisizer 3 Version 3.51" (manufactured by Beckman Coulter, Inc.) for setting measurement conditions and analyzing measurement data, and the weight average particle size (D4) is calculated by analyzing the measurement data.
[0192] The electrolyte solution used for the measurement is prepared by dissolving special grade sodium chloride in ion-exchanged water to a concentration of approximately 1% by mass, for example, "ISOTON II" (manufactured by Beckman Coulter).
[0193] Before performing measurements and analysis, the dedicated software is set up as follows.
[0194] In the "Change Standard Measurement Method (SOM) screen" of the dedicated software, set the total count number in the control mode to 50,000 particles, the number of measurements to 1, and the Kd value to the value obtained using "Standard Particle 10.0 μm" (Beckman Coulter). Press the threshold / noise level measurement button to automatically set the threshold and noise level. In addition, set the current to 1600 μA, the gain to 2, the electrolyte to ISOTON II, and check the aperture tube flush after measurement.
[0195] In the "Pulse to particle size conversion setting screen" of the dedicated software, set the bin interval to logarithmic particle size, the particle size bin to 256 particle size bins, and the particle size range to 2 μm to 60 μm.
[0196] The specific measurement method is as follows. (1) Pour about 200 mL of the electrolyte solution into a 250 mL round-bottom glass beaker made exclusively for the Multisizer 3, set it on the sample stand, and stir the stirrer rod counterclockwise at 24 revolutions per second. Then, use the "Aperture Tube Flush" function of the dedicated software to remove dirt and air bubbles from inside the aperture tube. (2) Approximately 30 mL of the electrolyte solution is placed in a 100 mL flat-bottom glass beaker, and approximately 0.3 mL of a solution prepared by diluting "Contaminon N" (a 10% by weight aqueous solution of a neutral detergent for cleaning precision measuring instruments with a pH of 7 consisting of a nonionic surfactant, anionic surfactant, and organic builder, manufactured by Wako Pure Chemical Industries, Ltd.) three times by weight with ion-exchanged water is added as a dispersant. (3) A specified amount of ion-exchanged water is placed in the water tank of an ultrasonic disperser "Ultrasonic Dispersion System Tetora150" (manufactured by Nikkaki Bios Co., Ltd.) that has two oscillators with an oscillation frequency of 50 kHz built in with a phase shift of 180 degrees and an electrical output of 120 W, and approximately 2 mL of Conaminon N is added to this water tank. (4) Set the beaker (2) in the beaker fixing hole of the ultrasonic disperser, operate the ultrasonic disperser, and adjust the height of the beaker so that the resonance state of the electrolyte solution in the beaker is maximized. (5) While the electrolyte solution in the beaker in (4) is irradiated with ultrasonic waves, about 10 mg of toner (particles) is added little by little to the electrolyte solution and dispersed. Then, ultrasonic dispersion treatment is continued for another 60 seconds. During ultrasonic dispersion, the water temperature in the water tank is appropriately adjusted to be 10°C or higher and 40°C or lower. (6) Using a pipette, add the electrolytic solution (5) in which the toner (particles) is dispersed to the round-bottom beaker (1) placed in the sample stand, and adjust the measurement concentration to about 5%. Then, measurements are continued until the number of particles measured reaches 50,000. (7) The measurement data is analyzed using the dedicated software that comes with the device, and the weight-average particle size (D4) is calculated. Note that when the dedicated software is set to Graph / Volume%, the "Average diameter" on the Analysis / Volume Statistics (Arithmetic Mean) screen is the weight-average particle size (D4). EXAMPLES
[0197] The basic configuration and features of the present invention have been described above. The present invention will now be described in more detail with reference to examples. Examples 5, 6, 10, 11, and 14 to 17 are reference examples. However, the present invention is not limited thereto in any way. In addition, unless otherwise specified, parts are based on mass.
[0198] <Production Example of First Resin 1 (Crystalline Resin C-1)> Solvent: toluene 100.0 parts Monomer composition 100.0 parts (The monomer composition is a mixture of behenyl acrylate, acrylonitrile, acrylic acid, and styrene in the ratio shown below. Behenyl acrylate: 60.0 parts Acrylonitrile: 10.0 parts Acrylic acid: 2.5 parts Styrene: 27.5 parts) Polymerization initiator 0.5 parts [t-Butyl peroxypivalate (NOF Corp.: Perbutyl PV)] The above materials were put into a reaction vessel equipped with a reflux condenser, a stirrer, a thermometer, and a nitrogen inlet tube under a nitrogen atmosphere. The reaction vessel was heated to 70°C while stirring at 200 rpm to carry out a polymerization reaction for 12 hours, thereby obtaining a solution in which the polymer of the monomer composition was dissolved in toluene.
[0199] Next, the temperature of the solution was lowered to 25°C, and then the solution was poured into 1000.0 parts of methanol while stirring to precipitate the methanol insoluble matter. The resulting methanol insoluble matter was filtered off, washed with methanol, and vacuum dried at 40°C for 24 hours to obtain a first resin 1 (crystalline resin 1). The weight average molecular weight (Mw) of the first resin 1 (crystalline resin 1) was 34000, the melting point (Tp) was 61°C, the acid value was 20.0 mgKOH / g, and the hydroxyl value was 0.0 mgKOH / g.
[0200] When the first resin 1 (crystalline resin 1) was analyzed by NMR, it was found to contain 20.0 mol% of monomer units derived from behenyl acrylate, 30.9 mol% of monomer units derived from acrylonitrile, 5.7 mol% of monomer units derived from acrylic acid, and 43.4 mol% of monomer units derived from styrene. In addition, the SP values (unit: (J / cm 3 )0.5) was calculated.
[0201] <Production Examples of First Resin (Crystalline Resins C-2 to C-4)> Using the monomers and the parts by mass as shown in Table 1, crystalline resins C-2 to C-4 were obtained in the same manner as in the production example of crystalline resin C-1.
[0202] <Production Example of First Resin (Crystalline Resin C-5)> 1,6-dodecanediol: 33.9 parts Dodecanedioic acid: 66.1 parts Tin 2-ethylhexanoate: 0.5 parts The above materials were weighed and placed in a reaction vessel equipped with a cooling tube, a stirrer, a nitrogen inlet tube, and a thermocouple. After replacing the atmosphere in the flask with nitrogen gas, the temperature was gradually raised with stirring, and the reaction was carried out for 3 hours at a temperature of 140°C with stirring.
[0203] Next, the pressure inside the reaction vessel was reduced to 8.3 kPa, and the reaction was carried out for 4 hours while maintaining the temperature at 200°C.
[0204] Thereafter, the pressure in the reaction vessel was reduced to 5 kPa or less, and the mixture was reacted at 200° C. for 3 hours to obtain a crystalline resin C-5.
[0205] [Table 1] The abbreviations in Table 1 are as follows: BEA: Behenyl acrylate SA: stearyl acrylate MYA: Myrisil acrylate GEA: Gedyl acrylate HDA: 1,6-Hexanediol AN: Acrylonitrile AA: Acrylic acid
[0206] <Production Example of Second Resin (Amorphous Resin A-1)> An autoclave was charged with 50.0 parts of xylene and purged with nitrogen, and then the temperature was raised to 185° C. in a sealed state with stirring.
[0207] A mixed solution of 75.0 parts of styrene, 15.5 parts of n-butyl acrylate, 1.1 parts of divinylbenzene, 9.5 parts of acrylonitrile, 0.5 parts of acrylic acid, 1.5 parts of di-tert-butyl peroxide, and 20.0 parts of xylene was continuously added dropwise to the autoclave for 3 hours while controlling the temperature inside the autoclave at 185° C. to polymerize.
[0208] The temperature was maintained for another hour to complete the polymerization, and the solvent was removed to obtain a second resin A-1 (amorphous resin A-1). The softening point (Tm) of the second resin was 110°C.
[0209] <Production Examples of Second Resin (Amorphous Resins A-2 to A-5)> Using the monomers and the parts by mass as shown in Table 2, amorphous resins A-2 to A-5 were obtained in the same manner as in the production example of amorphous resin A-1.
[0210] [Table 2] The abbreviations in Table 2 are as follows: St: styrene BA: n-butyl acrylate AN: Acrylonitrile
[0211] <Production Example of Second Resin (Amorphous Resin A-6)> (Polyester resin formulation) Bisphenol A propylene oxide (2.0 mol adduct) 100.0 mol parts Terephthalic acid 95.0 mol parts Acrylic acid 5.0 mol parts 90 parts of the mixture of monomers for forming the polyester resin was charged into a four-neck flask, which was equipped with a pressure reducing device, a water separating device, a nitrogen gas introducing device, a temperature measuring device and a stirring device, and stirred at 160° C. in a nitrogen atmosphere.
[0212] To the mixture, 10 parts of a vinyl polymerizable monomer (a mixture of 80.0 parts of styrene, 19.0 parts of n-butyl acrylate, and 1.0 part of acrylic acid) for producing a vinyl resin and 1 part of benzoyl peroxide as a polymerization initiator were added dropwise from a dropping funnel over a period of 4 hours, and the mixture was allowed to react at 160°C for 5 hours.
[0213] Thereafter, the temperature was raised to 230°C, and 0.2 parts of titanium tetrabutoxide was added per 100 parts of the total amount of monomers forming the polyester resin, and polymerization was carried out until the softening point reached 120°C.
[0214] After the reaction was completed, the resin was removed from the vessel, cooled, and pulverized to obtain amorphous resin A-6. The SP value was 23.7 and the Tm was 120°C.
[0215] <Production Example of Toner Particle 8> ·Crystalline resin C-1 35.0 parts Amorphous resin A-1 65.0 parts 5.0 parts wax 1 (Fischer-Tropsch wax; maximum endothermic peak temperature 90℃) Colorant 1 9.0 parts (Cyan pigment made by Dainichi Seika: Pigment Blue 15:3) The above materials were mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 20 s -1 After mixing for 5 min, the mixture was kneaded in a twin-screw kneader (PCM-30, Ikegai Corporation) set at 130°C with a screw rotation speed of 250 rpm and a discharge temperature of 130°C. The kneaded mixture was cooled and then coarsely crushed to 1 mm or less using a hammer mill to obtain a coarsely crushed product. The coarsely crushed product was then finely crushed using a mechanical grinder (T-250, Freund Turbo Corporation).
[0216] Further, classification was performed using Faculty F-300 (manufactured by Hosokawa Micron Corporation) to obtain toner particles 8 having a weight average particle size (D4) of about 6.0 μm. The operating conditions were a classification rotor rotation speed of 130 s -1 , Dispersion rotor speed 120s -1 It was decided.
[0217] <Production Examples of Toner Particles 1-7 and 9-21> The combinations of the first resin (crystalline resin) and the second resin (amorphous resin) were as shown in Table 3, and the same production method as in the production example of toner particle 8 was used to obtain toner particles 2 to 21.
[0218] However, toner particles 7 were obtained by mixing toner particles obtained by kneading at a discharge temperature of 130°C by the above method and toner particles obtained by kneading at a discharge temperature of 110°C. Toner particles 1 to 6 were obtained by combining toner particles obtained by kneading at a discharge temperature of 130°C, toner particles obtained by kneading at 120°C, and toner particles obtained by kneading at 110°C. Toner particles 14 were obtained by kneading at the screw rotation speed of 300 rpm and the discharge temperature of 110°C. Toner particles 15 were obtained by kneading at the screw rotation speed of 180 rpm and the discharge temperature of 145°C. Toner particles 16 were obtained by kneading at the screw rotation speed of 320 rpm and the discharge temperature of 100°C. Toner particles 17, 20, and 21 were obtained by kneading at the screw rotation speed of 140 rpm and the discharge temperature of 150°C.
[0219] For each case, the difference (Tm-Tp) between the Tm of the second resin and the Tp of the first resin, and the value |SPc-SPa| where SPc is the SP value of the first resin and SPa is the SP value of the second resin are also shown in Table 3.
[0220] [Table 3]
[0221] <Production Examples of Toners 1 to 21> The obtained toner particles 1 were subjected to a heat treatment by the surface treatment device shown in FIG. 1 to obtain heat-treated toner particles. The operating conditions were a feed rate of 3 kg / hr, a hot air temperature of 130° C., and a hot air flow rate of 6 m 3 / min., cold air temperature = -5℃, cold air flow rate = 4m 3 / min., Blower air volume = 20m 3 / min., Injection air flow rate = 1m 3 / min.
[0222] The obtained heat-treated toner particles 1 (100 parts) were surface-treated with 4% by mass of hexamethyldisilazane to obtain a toner having a BET specific surface area of 25 m 2 / g hydrophobic silica fine particles, 0.5 parts, BET specific surface area 100 m 2 0.5 parts of hydrophobic silica particles / g were added, and the mixture was mixed in a Henschel mixer (FM-75, manufactured by Nippon Coke and Engineering Co., Ltd.) at a rotation speed of 30 s -1 The mixture was mixed for 10 minutes with a rotation time of 10 minutes to obtain Toner 1.
[0223] For the toner particles 2 to 21, the same heat treatment and external addition of silica fine particles as above were carried out to obtain toners 2 to 21, respectively.
[0224] Table 4 shows the measurement results of the area ratio of the matrix, the average circularity and standard deviation of the circularity of the domains, and the number-average circle-equivalent diameter of the domains.
[0225] [Table 4]
[0226] <Magnetic Carrier 1 Manufacturing Example> Number average particle size: 0.30μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 1 Number average particle size: 0.50μm, magnetization strength under a magnetic field of (1000 / 4π(kA / m): 65Am 2 / kg) of magnetite 2 To 100 parts of each of the above materials, 4.0 parts of a silane compound (3-(2-aminoethylaminopropyl)trimethoxysilane) was added, and the mixture was mixed and stirred at high speed in a container at 100° C. or higher to treat each of the fine particles. Phenol: 10% by weight Formaldehyde solution: 6% by mass (40% by mass of formaldehyde, 10% by mass of methanol, 50% by mass of water) Magnetite treated with the above silane compound 1:58 mass% Magnetite treated with the above silane compound 2: 26% by mass 100 parts of the above material, 5 parts of a 28% by mass aqueous ammonia solution, and 20 parts of water were placed in a flask, and the mixture was heated to 85°C over 30 minutes and held at that temperature while stirring and mixing. A polymerization reaction was carried out for 3 hours, and the resulting phenolic resin was cured.
[0227] Thereafter, the hardened phenolic resin was cooled to 30° C., and water was further added thereto. The supernatant liquid was then removed, and the precipitate was washed with water and then air-dried.
[0228] This was then dried under reduced pressure (5 mmHg or less) at a temperature of 60° C. to obtain magnetic material-dispersed spherical magnetic carrier 1. The volume-based 50% particle diameter (D50) of magnetic carrier 1 was 34.2 μm.
[0229] <Production example of two-component developer 1> Toner 1 (8.0 parts) was added to magnetic carrier 1 (92.0 parts), and mixed in a V-type mixer (V-20, manufactured by Seishin Enterprises) to obtain two-component developer 1.
[0230] <Production Examples of Two-Component Developers 2 to 21> Two-component developers 2 to 21 were obtained in the same manner as for two-component developer 1, except that toners 2 to 21 were used instead of toner 1, respectively.
[0231] Example 1 The above two-component developer 1 was used for evaluation.
[0232] A modified Canon imageRUNNER ADVANCE C5560 digital commercial printer was used as the image forming apparatus, and two-component developer 1 was placed in the cyan developer. The apparatus was modified so that the fixing temperature, process speed, developer carrier DC voltage VDC, electrostatic latent image carrier charging voltage VD, and laser power could be freely set. The image output evaluation was performed by outputting a FFh image (solid image) with a desired image ratio, and adjusting VDC, VD, and laser power so that the amount of toner on the FFh image on the paper was as desired, and then performing the following evaluation.
[0233] FFh is a hexadecimal value representing 256 gradations, with 00h being the first gradation (white background) of the 256 gradations, and FFh being the 256th gradation (solid area) of the 256 gradations.
[0234] [Image gloss evaluation] ·Paper: GFC-081 (81.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 0.40mg / cm 2 (Adjusted by DC voltage VDC of developer carrier, charging voltage VD of electrostatic latent image carrier, and laser power) Evaluation image: Place a 2cm x 5cm image in the center of the A4 paper. Test environment: Temperature 23℃ / Humidity 50%RH Fixing temperature: 160℃ Process speed: 400mm / sec The above evaluation image was output, and the image glossiness was evaluated. The image glossiness was evaluated using a handy glossmeter (Tokyo Denshoku Co., Ltd.'s "PG-1M") to measure the value at a single angle of 60°, and the measured value was used as the gloss value. The evaluation results are shown in Table 5.
[0235] (Image gloss evaluation standard) A: 8 or above (very good) B: 5 or more and less than 8 (good) C: 2 or more and less than 5 (a level that is not problematic in the present invention) D: Less than 2 (not acceptable in the present invention)
[0236] [Low temperature fixability] ·Paper: GFC-081 (81.0g / m 2 ) (Sold by Canon Marketing Japan Inc.) Toner load on paper: 0.70mg / cm 2 (Adjusted by DC voltage VDC of developer carrier, charging voltage VD of electrostatic latent image carrier, and laser power) Evaluation image: Place a 2cm x 5cm image in the center of the A4 paper. Test environment: Low temperature and low humidity environment: Temperature 15℃ / Humidity 10%RH (hereinafter referred to as "L / L") Fixing temperature: 140℃ Process speed: 400mm / sec The above evaluation image was output, and the low-temperature fixing property was evaluated. The image density reduction rate was used as an evaluation index for the low-temperature fixing property.
[0237] The image density reduction rate was measured using an X-Rite color reflection densitometer (500 series: manufactured by X-Rite Corporation). First, the image density in the center was measured. Next, the area where the image density was measured was subjected to 4.9 kPa (50 g / cm 2 The fixed image is rubbed (five times back and forth) with Silbon paper under a load of 1000 g / m2, and the image density is measured again.
[0238] The rate of decrease in image density before and after rubbing was calculated using the following formula. The rate of decrease in image density obtained was evaluated according to the following evaluation criteria. The evaluation results are shown in Table 5. Image density decrease rate=(image density before friction−image density after friction) / (image density before friction)×100
[0239] (Evaluation Criteria) A: Image density reduction rate is less than 3.0% B: Image density reduction rate: 3.0% or more and less than 5.0% C: Image density reduction rate: 5.0% or more and less than 8.0% D: Image density reduction rate 8.0% or more
[0240] [Evaluation of toner blocking resistance (heat-resistant storage stability)] In order to evaluate the stability during storage, blocking resistance was evaluated. Approximately 5 g of toner was placed in a 100 ml resin cup and left for 10 days in an environment with a temperature of 50°C and a humidity of 20%, after which the degree of cohesion of the toner was measured as follows and evaluated according to the following criteria.
[0241] The measuring device used was a "Powder Tester" (manufactured by Hosokawa Micron Corporation) with a digital display vibration meter "DigiVibro MODEL 1332A" (manufactured by Showa Sokki Co., Ltd.) connected to the side of the vibration table. A sieve with a mesh size of 38 μm (400 mesh), a sieve with a mesh size of 75 μm (200 mesh), and a sieve with a mesh size of 150 μm (100 mesh) were placed on top of each other on the vibration table of the powder tester from the bottom up. The measurements were carried out in an environment of 23°C and 60% RH as follows. (1) The vibration amplitude of the vibration table was adjusted in advance so that the displacement value on the digital display vibrometer was 0.60 mm (peak-to-peak). (2) The toner that had been left for 10 days as described above was left for 24 hours in an environment of 23° C. and 60% RH in advance, and 5 g of the toner was precisely weighed out and gently placed on the top sieve with 150 μm openings. (3) After the sieves were vibrated for 15 seconds, the mass of the toner remaining on each sieve was measured and the degree of cohesion was calculated according to the following formula. Coagulation degree (%) = {(mass of sample on 150 μm mesh sieve (g)) / 5 (g)} × 100 + {(Sample mass (g) on 75 μm mesh sieve) / 5(g)} x 100 x 0.6 + {(Sample mass (g) on 38 μm mesh sieve) / 5(g)} x 100 x 0.2
[0242] The evaluation criteria are as follows, and a grade of C or higher was determined to indicate that the effects of the present invention were achieved. The evaluation results are shown in Table 5. A: Coagulation rate is less than 20% B: The degree of aggregation is 20% or more but less than 25%. C: Coagulation degree is 25% or more and less than 35%. D: Cohesion degree is 35% or more.
[0243] [Examples 2 to 17 and Comparative Examples 1 to 4] Evaluation was performed in the same manner as in Example 1, except that two-component developers 2 to 21 were used instead of two-component developer 1. The evaluation results are shown in Table 5.
[0244] [Table 5]
Claims
1. A method for producing a toner having toner particles containing a binder resin, comprising the steps of: The production method comprises the steps of: A melt-kneading step of melt-kneading the first resin and the second resin to obtain a resin composition; and a grinding step of grinding the obtained resin composition; The toner particles are obtained through the binder resin contained in the toner particles contains a first resin and a second resin, The first resin comprises: (i) a crystalline vinyl resin containing an acrylonitrile unit, (ii) the melting point Tp is 50° C. or more and 90° C. or less; The second resin is (i) an amorphous styrene-acrylic resin containing an acrylonitrile unit, (ii) the softening point Tm is 10° C. or more higher than the Tp; the toner particles have a matrix domain structure having a matrix of the first resin and a domain of the second resin when a cross section of the toner particles is observed with a transmission electron microscope; The average circularity of the domains is from 0.40 to 0.
80.
2. 2. The method for producing a toner according to claim 1, wherein the domains have a number-average circle-equivalent diameter of 20 nm to 500 nm.
3. When the SP value of the first resin is SPc and the SP value of the second resin is SPa, the SPc and the SPa are 0.5≦|SPc-SPa|≦2.0 The method for producing a toner according to claim 1 or 2, which satisfies the above condition.
4. 4. The method for producing a toner according to claim 1, wherein, in cross-sectional observation by the transmission electron microscope, the first resin accounts for 35% or more and 70% or less of a combined area of the matrix and the domain.
5. The method for producing a toner according to claim 1 , wherein the first resin has a monomer unit represented by the following formula (1): 【Chemistry 1】 [In formula (1), R Z1 represents a hydrogen atom or a methyl group, R 1 represents an alkyl group having 18 to 36 carbon atoms.
6. The method for producing a toner according to claim 1 , wherein a standard deviation of circularity of the domain containing the second resin is 0.15 or more.
7. The method for producing a toner according to claim 1 , wherein the crystalline vinyl resin has an acrylonitrile unit content of 5.0% by mass or more and 40.0% by mass or less.
Citation Information
Patent Citations
Toner, developer, and image forming apparatus
JP2014066994A
Toner
JP2014142632A
Toner binder and toner
JP2018156074A
Toner binder and toner
JP2019139213A
Toner and method for manufacturing toner
JP2019219643A